Building Unity: Roblox Community's Twitter Response to Affan Kurniawan Tragedy - Sinaga, Joyce Chardha; Azahra, Naiya; Moesa, Raga Michael Nevada; Jocelym, Evaness; Rangkuti, Rahmadsyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores how members of the Indonesian Roblox community used language on Twitter to express solidarity and organize fundraising efforts following the tragic death of Affan Kurniawan during a demonstration, aiming to analyze the linguistic strategies this gaming community employed to build a collective identity and coordinate charitable actions across digital platforms. The study examined 23 Twitter comments from Indonesian Roblox community members, selected through purposive sampling based on their participation in fundraising discussions and memorial activities related to the Affan Kurniawan case. Using Critical Discourse Analysis with Van Dijk’s three-dimensional framework, the research analyzed macrostructure (thematic organization), superstructure (discourse schemas), and microstructure (semantic, syntactic, lexical, and stylistic elements) through a qualitative examination of linguistic patterns and discourse strategies. The analysis revealed five primary thematic domains: Memorial and Commemoration, Donation and Financial Support, Gaming Platform Integration, Social Justice and Political Critique, and Community Solidarity and Collective Identity, with Gaming Platform Integration emerging as a novel form of digital activism. The findings showed that community members strategically used code-switching between Indonesian and English, Islamic terminology, gaming-specific vocabulary, and varied syntactic structures to maintain cultural authenticity while facilitating cross-platform activism. The study concludes that gaming communities possess unique linguistic capabilities for social organizing that extend beyond traditional social media activism, contributing new insights to digital discourse analysis and revealing how marginalized communities can leverage unconventional digital resources to create effective solidarity networks and organize meaningful collective action in response to social injustices.